2014
DOI: 10.1155/2014/489382
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil Ameliorates Gentamicin-Induced Nephrotoxicity in Rats: Role of iNOS and eNOS

Abstract: Gentamicin, an aminoglycoside antibiotic, is used for the treatment of serious Gram-negative infections. However, its usefulness is limited by its nephrotoxicity. Sildenafil, a selective phosphodiesterase-5 inhibitor, was reported to prevent or decrease tissue injury. The aim of this study is to evaluate the potential protective effects of sildenafil on gentamicin-induced nephrotoxicity in rats. Male Wistar rats were injected with gentamicin (100 mg/kg/day, i.p.) for 6 days with and without sildenafil. Sildena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 27 publications
3
22
1
Order By: Relevance
“…Another study has reported that antioxidant vitamins can elicit NO level and improve endothelial functioning (28). Contrary to our findings, Morsy at al, documented that GM could increase NO level (20). Other studies reported that NO does not have any important role in renal hemodynamic.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Another study has reported that antioxidant vitamins can elicit NO level and improve endothelial functioning (28). Contrary to our findings, Morsy at al, documented that GM could increase NO level (20). Other studies reported that NO does not have any important role in renal hemodynamic.…”
Section: Discussioncontrasting
confidence: 97%
“…Enormous studies have shown some contradictory effects on serum and kidney level of NO. For example, Sadeghi et al reported that after administration of GM, serum and kidney levels of NO decreased (19), while Morsy et al documented that GM increased nitrite levels (20).…”
Section: Introductionmentioning
confidence: 99%
“…In gentamicin-induced nephrotoxicity in rats, sildenafil significantly decreased serum creatinine, urea, urinary albumin excretion, renal malondialdehyde, and nitrite/nitrate levels, with a concomitant increase in renal catalase and superoxide dismutase activities and an improvement in histological injury, compared to gentamicin-treated control rats [44].…”
Section: Nephrototoxic Nephropathymentioning
confidence: 80%
“…Regarding the level of total renal tissue (NO), the results obtained in this study displayed that it was significantly higher in diabetic rats than in the control rats. (Morsy et al, ) reported that NO production induced by inducible NO synthase (iNOS) increased by hyperglycemia, and increased the accumulation of the extracellular matrix in mesangial cells. At toxic concentrations that is produced by the iNOS, its “bad face” appears as leading to the renal inflammatory state through peroxynitrite (ONOO − ) formation, a proinflammatory cytokine, by reacting with superoxide anion (O 2 •− ).…”
Section: Discussionmentioning
confidence: 99%